Transplant-Associated Thrombotic Microangiopathy (TA-TMA) in Childhood - A literature review - Shamsian, Bibi Shahin (Journal of Pediatric Nephrology, 2015)
Transplant-associated thrombotic microangiopathy (TA-TMA) is considered one of the most severe complications after hematopoietic stem cell transplantation (HSCT). Transplant-associated thrombotic microangiopathy (TA-TMA) constitutes a form of microangiopathic haemolytic anemia and thrombocytopenia derived from a generalized endothelial dysfunction with intravascular platelet activation and formation of platelet-rich thrombi within the microcirculation. Since clinical features are common in several post hematopoietic stem cell transplantation (HSCT) complications such as capillary leak syndrome, engraftment syndrome, graft versus host disease (GVHD), diffuse alveolar hemorrhage and veno occlusive disease (VOD), an initial diagnosis of TA-TMA is not always certain, which is a principal reason for the failure of proposed treatments. Keywords: Thrombotic Microangiopathies; Hematopoietic Stem Cell Transplantation; Child; Hemolytic-Uremic Syndrome; Eculizumab. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–>